Erratum: Adiabatic speedup via zero-energy-change control in a spin system. (7th March 2019) - Zhang, Li-Cheng; Ren, Feng-Hua; Chen, Yi-Fei; He, Run-Hong; Gu, Yong-Jian; Wang, Zhao-Ming
Abstract: Original article: EPL, 125 (2019) 10010 .